2015
DOI: 10.20473/jbe.v3i1.2015.57-68
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Family Support with the Quality of Life of Patients with Diabetes Mellitus

Abstract: Diabetes mellitus is a disease that will accompany a lifetime and require long term treatment so that it can reduce quality of life of the patients. This study aim to analyze the correlation between family support with the quality of life of patients with diabetes mellitus. This study was analytic observational with cross-sectional design. The population was all patients with diabetes mellitus who visited Tanah Kalikedinding Health Center in January to March 2014. Patients was diagnosed diabetes mellitus throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…The family support has an impact on the physical and mental health of its members. Poor family support is associated with an increase in morbidity and mortality [38].…”
Section: Resultsmentioning
confidence: 99%
“…The family support has an impact on the physical and mental health of its members. Poor family support is associated with an increase in morbidity and mortality [38].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with diabetes mellitus need family support to optimize their treatment management. By regulating and facilitating behavior change, family support can improve the quality of life for diabetes mellitus patients (Retnowati Satyabakti, 2015). Family support is also needed to overcome the feelings of worry and the emotional burden of diabetes mellitus patients (Rahmi et al, 2020).…”
Section: The Relationship Betweenmentioning
confidence: 99%
“…This was quite different when compared to the results of previous studies. Several studies have been conducted to identify the relationship between family support and quality of life, especially in patients with chronic diseases such as the research conducted by Prazeres and Santiago (2016), Retnowati & Satyabakti (2015) and Barutcu et al (2013). All three concluded that there was a relationship between family support and quality of life.…”
Section: Family Support and Quality Of Lifementioning
confidence: 99%
“…Family support which is part of social support can be defined as the attitude of family acceptance of family members that can be demonstrated by the actions of other family members. The family considers that all family members are part of the family that cannot be separated and view the family as the person closest to him (Setiabudi in Retnowati & Satyabakti, 2015). Family support has four dimensions or components, namely emotional support, informative support, instrumental support and reward support (Friedman, 2010).…”
Section: Introductionmentioning
confidence: 99%